A Biofuel Cell Based on Biocatalytic Reactions of Lactate on Both Anode and Cathode Electrodes – Extracting Electrical Power from Human Sweat. Issue 6 (29th March 2017) - Koushanpour, Ashkan; Gamella, Maria; Katz, Evgeny
Abstract: Electrodes composed of carbon fibers were modified with graphene nano‐sheets in order to increase their surface area and facilitate electrochemical reactions. Electrocatalytic species, such as Meldola's blue (MB) and hemin were immobilized on the graphene surface due to their π‐π stacking and then used for electrocatalytic oxidation of NADH and reduction of H2 O2, respectively. Further modification of these electrodes with enzymes producing NADH and H2 O2 in situ (lactate dehydrogenase, LDH, and lactate oxidase, LOx, respectively), allowed assembling of a biofuel cell operating in the presence of lactate, oxygen and NAD + . The cathode of the biofuel cell required lactate and O2 for its operation, while the anode operated in the presence of lactate and NAD + . Notably, both bioelectrocatalytic electrodes operated in the presence of lactate, one producing H2 O2 in the reaction catalyzed by LOx in the presence of O2, second producing NADH in the reaction catalyzed by LDH in the presence of NAD + . Both reactions were performed in the biofuel cell without separation of the cathodic and anodic solutions and with no need of a membrane. The biofuel cell was tested in solutions mimicking human sweat and then in real human sweat samples, demonstrating substantial power release being able to activate electronic devices. Abstract : A biofuel cell operating in human sweat sample was used to activate an electronic watch as an example micro‐electronic device.